All‐Recyclable Triboelectric Nanogenerator for Sustainable Ocean Monitoring Systems (Adv. Energy Mater. 30/2022). Issue 30 (11th August 2022) - Ahn, Junseong; Kim, Ji‐Seok; Jeong, Yoonsang; Hwang, Soonhyoung; Yoo, Hyunjoon; Jeong, Yongrok; Gu, Jimin; Mahato, Manmatha; Ko, Jiwoo; Jeon, Sohee; Ha, Ji‐Hwan; Seo, Hee‐Seon; et al.
Abstract : Triboelectric Nanogenerators In article number 2201341, Jun‐Ho Jeong, Il‐Kwon Oh, Inkyu Park and co‐workers develop an all‐recyclable triboelectric nanogenerator (AR‐TENG) that exhibits high power density and excellent mechanochemical stability. The recyclability is demonstrated through its disassembly and fabrication of a plasmonic color filter. An ocean energy harvesting system based on the AR‐TENG is developed and used to power a buoy‐type ocean monitoring system and intelligent life jacket.